La cordillera oriental colombiana no se desprende de la cordillera central (1999)
Geologically the Central and Eastern Cordilleras depict different periods of genesis and different types of rocks which allow them to keep their identities and independence from Colombia to Bolivia; however, in the area of study are connected by a bridge formed by a recent geomorphollogical feature which is the result of combined tectonic and volcanic stresses which took place toward the end of the Pliocene. This bridge has a direction NW-SE and connects the Cutanga Volcanoe on the Central Cordillera with the Highs of La Fragua on the Eastern Cordillera and is recognized as Serranía de La Fragua. This Serranía of La Fragua has been poorly examined in the geographic sense, and ignored geologically.  In order to justify its presence, two hypothesis are presented, where mainly deep fracturing, plus uplifting and subordinately the emission of ignimbrites or basaltic lava flows along the aligned volcanic centres developed on the fracture systems. These lava flows formed a high plain which is presently dissected and diminished. According with known data the high plain is preferentially formed byignimbrlles.  The preservation of this high plain between 2.700 and 3.000 meters above sea level as a result of a relative resistance to the erosion, is the main cause of the bridge between the Central and Eastern Cordilleras which for more than 100 years has suggested the bifurcation of the two cordilleras. Unfortunately this idea is erroneous, but has been accepted in Colombia and also in foreign countries. The Tectonic Depression of the Upper Magdalena Valley (VSM) is a continuous feature that virtually disappears close to Mocoa, at the Guairapungo lineament; however it could continue all the way to Ecuador as a very narrow strip. This depression has a general strike NNE-SSW and possibly was inidally uninterrupted all the way. lt has been divided in several sub- basins due to differential movements of deep old faults, with general strikes NW- SE, which have been named Lineaments. In the area the Lineaments of Guairapungo, La Fragua, Puracé and Suérez are identified.  The knowledge related to the last andean paroxysm and the relationship with volcanic activity is reduced. The lineaments previously mentioned have been reactivated in the last stages of the Andean orogeny, mainly connected with basaltic emissions, as well as geoformes formed by riolitic and dacitic events.  The stratigraphic relationship between the different geologic units have not been well defined. It is urgent to conduct a well detailed stratigraphic analysis of the mountain area, known as Caquetá High Basin, which has been considered as part of the Putumayo Basin.